The Effect of Tides on Plankton Communities in the Belawan River Estuary, North Sumatra - Leidonald, Rusdi; Muhtadi, Ahmad; Harahap, Cici Maulidiah; Mukra, Rizal; Ishak, Mohd Yusoff; Hasani, Qadar (HAYATI Journal of Biosciences, 2026)
The Belawan Estuary is a highly important economic and logistics hub in Sumatra, serving as the primary maritime transportation route in western Indonesia. This estuary is also utilized for multiple purposes, including industrial activity, residential areas, and fisheries. These activities inevitably influence water quality, which in turn affects the presence and population dynamics of plankton in the estuary. This study aimed to examine the spatial and temporal distribution of plankton communities in the Belawan Estuary. Observation points were selected from eight locations representing different activities and regions, including areas near the sea, the middle section, and areas close to land. Plankton samples were collected during high and low tides following the tidal cycle (new moon, first quarter, full moon, and last quarter). Principal component analysis was performed to determine the influence of tidal cycles on plankton composition and abundance in the estuary. A total of 64 plankton genera from 16 classes were identified in the estuary. spatially, the highest abundance was recorded in the mouth estuary during low tide. Temporally, the highest plankton abundance across stations was during the first quarter phase at low tide. These findings indicate that tidal cycles significantly influence plankton abundance in the Belawan Estuary. This phenomenon is attributed to the tidal currents that transport nutrients from the lower layers to the surface waters during both high and low tides. Changes in plankton abundance and species composition can serve as indicators of water fertility in this region and reflect the impacts of changes in environmental conditions.